ADAPTIVE HIERARCHICAL CYBER ATTACK DETECTION AND LOCALIZATION IN ACTIVE DISTRIBUTION SYSTEMS - SAHIK IMRAN,HARSHITHA, CHANDANA, DIVIJA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Recently, Cyber Physical System (CPS) is one of the core technologies for realizing Internet of Things (IoT). The CPS is a new paradigm that seeks to converge the physical and cyber worlds in which we live. However, the CPS suffers from certain CPS issues that could directly threaten our lives, while the CPS environment, including its various layers, is related to on-the-spot threats, making it necessary to study CPS security. Therefore, a survey-based in-depth understanding of the vulnerabilities, threats, and attacks is required of CPS security and privacy for IoT. In this paper, we analyze security issues, threats, and solutions for IoT-CPS, and evaluate the existing researches. The CPS raises a number challenges through current security markets and security issues. The study also addresses the CPS vulnerabilities and attacks and derives challenges. Finally, we recommend solutions for each system of CPS security threats, and discuss ways of resolving potential future issues